All-solid-state lithium-ion batteries with TiS2 nanosheets and sulphide solid electrolytes. Issue 26 (17th June 2016) - Oh, Dae Yang; Choi, Young Eun; Kim, Dong Hyeon; Lee, Young-Gi; Kim, Byeong-Su; Park, Jongnam; Sohn, Hiesang; Jung, Yoon Seok
Abstract : TiS2 nanosheets (TiS2 -NSs) prepared by scalable mechanochemical lithiation, followed by exfoliation in water under ultra-sonication, exhibit excellent electrochemical performance for sulphide-SE-based bulk-type ASLBs. Abstract : Bulk-type all-solid-state lithium-ion batteries (ASLBs) using sulphide solid electrolytes (SEs) are considered as one of the promising alternative batteries because of their ultimate safety and scalable fabrication. However, they suffer from poor ionic contacts between active materials and SEs. Herein, we report, for the first time, the excellent electrochemical performances of sulphide-SE-based bulk-type ASLBs employing TiS2 nanosheets (TiS2 -NSs) prepared by scalable mechanochemical lithiation, followed by exfoliation in water under ultrasonication. The TiS2 -NS in all-solid-state cells exhibits an enhancement of reversible capacity which is attributed to the SE region in intimate contact with TiS2 -NSs. Importantly, an exceptionally superior rate capability of the TiS2 -NS compared to that of bulk TiS2 and even ball-milled TiS2, which is attributed to the ultrathin 2D structure (with short Li-ion diffusion length and intimate contacts between the TiS2 -NS and SE) and high electronic conductivity, is highlighted.